Assessing Chemotherapy-Induced Peripheral Neuropathy in Postmenopausal Breast Cancer Patients Using Vibration Perception Threshold - Nielsen, August; Marstrand, Simone Diedrichsen; Marina, Djordje; Andersson, Michael; Jensen, Lars Thorbjørn; Buch-Larsen, Kristian; Schwarz, Peter (Cancer investigation, 2025)
This study investigated the 3-year development of chemotherapy-induced peripheral neuropathy (CIPN) in post-menopausal women diagnosed with early breast cancer (EBC) using vibration perception threshold (VPT) measurements and the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (CIPN18). 90 patients (aged 50-70) and 30 healthy subjects were included in the study. VPT measurements and CIPN18 questionnaires were performed post-chemotherapy (median 72 (IQR: 53-93) days post chemotherapy) as well as at the 12 and 36-month follow-up. Post-chemotherapy data showed impaired VPT measurements when comparing our study population to controls, but spontaneous improvement occurred, and by the 36-month follow-up, VPT measurements normalized when compared to controls. Mean CIPN18 scores improved, though the improvement was not statistically significant. Spearman's rho between VPT measurements and CIPN18 questionnaires showed weak to moderate correlations during follow-up. However, further analyses using a Generalized Additive Model confirmed the absence of a significant correlation between VPT measurements and CIPN18 questionnaires. Our data highlight limitations in the relationship between VPT measurements and CIPN. However, VPT measurements may have potential as an objective supplement to general assessment of patients.